Dissipation of Impact Stress Waves within the Artificial Blasting Damage Zone in the Surrounding Rocks of Deep Roadway - Jianguo Ning; Jun Wang; Yunliang Tan; Xinshuai Shi (Shock and Vibration)
Artificial explosions are commonly used to prevent rockburst in deep roadways. However, the dissipation of the impact stress wave within the artificial blasting damage zone (ABDZ) of the rocks surrounding a deep roadway has not yet been clarified. The surrounding rocks were divided into the elastic zone, blasting damage zone, plastic zone, and anchorage zone in this research. Meanwhile, the ABDZ was divided into the pulverizing area, fractured area, and cracked area from the inside out. Besides, the model of the normal incidence of the impact stress waves in the ABDZ was established; the attenuation coefficient of the amplitude of the impact stress waves was obtained after it passed through the intact rock mass, and ABDZ, to the anchorage zone. In addition, a numerical simulation was used to study the dynamic response of the vertical stress and impact-induced vibration energy in the surrounding rocks. By doing so, the dissipation of the impact stress waves within the ABDZ of the surrounding rocks was revealed. As demonstrated in the field application, the establishment of the ABDZ in the surrounding rocks reduced the effect of the impact-induced vibration energy on the anchorage support system of the roadway.